Teaching Islamic Studies in the Age of ISIS, Islamophobia, and the Internet - Tumin Tumin (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2020)
Teaching Islamic Studies in the Age of ISIS, Islamophobia, and the Internet is a collection of articles by contributors who have been teaching classes about Muslims and Islam especially in the Western contexts. This book is edited by Courtney M. Dorroll, an Assistant Professor of Middle Eastern and North African Studies at Wofford College in South Carolina. As an academic at a small college, the editor is alert to the challenges presenting advices on how to teach this important but sensitive issue of Islam to new academics and students in the communities. In the age of misrepresentations and stereotypes of Islam, this book is considered important to teachers and students as a means to encourage them to thoughtfully engage with the topic of Islam. The original idea of Teaching Islamic Studies in the Age of ISIS, Islamophobia, and the Internet is initiated from a talk given by Richard C. Martin, a Professor Emeritus of Religion at Emory University. He gave a talk at Wofford College under an invitation from the editor of this book, Courtney M. Dorroll. Professor Martin has written and edited several books including Defenders of Reason in Islam: Mutazilism from Medieval School to Modern Symbol and Rethinking Islamic Studies: From Orientalism to Cosmopolitanism. In this book, the contributors especially shared their personal struggles and address the challenges of teaching about Islamic religion while the media mostly promote Islamophobia and violence. They proposed some approaches to Islamic studies pedagogy and provided some suggestions to better structure the course. These approaches and suggestions are based on their own experiences facing the students and parents who might initially fear the topic related to Muslims and Islam. In order to encourage a deeper engagement in this course, the contributors include collaborative teaching models by doing reading and media suggestions. This approach will result in a broader thinking of students on this subject. It can be said that by reading this particular book, students are exposed to challenging ideas of Islamophobia and encouraged to confront these ideas fairly and objectively. More importantly, this book provides a fair and open discussion of an important issue in teaching about Islam.